2020
DOI: 10.1016/j.jdiacomp.2020.107691
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to educe severe diabetic foot nfections and complications uring pidemics (STRIDE)

Abstract: Aims Patients with diabetes, including those with foot complications, are at highest risk for severe outcomes during the COVID-19 pandemic. Diabetic foot ulcers (DFU) present additional challenges given their superimposed risk for severe infections and amputations. The main objectives were to develop a triage algorithm to effectively risk-stratify all DFUs for potential complications, complying with social distancing regulations, preserving personal protective equipment, and to assess feasibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(65 citation statements)
references
References 25 publications
0
62
1
2
Order By: Relevance
“…Other authors have also noticed an increased rates of major or minor amputations during the pandemic period attributed to predominantly ischemic ulcers or non infected DFU [ 23 25 ]. The amputation rates in our study was significantly less as compared to that observed by Caruso P, et al [ 21 ] and Schmidt et al [ 22 ] despite the inclusion of patients with active DFU (either ischemic or neuropathic) with or without DFI. Probable reasons for lesser amputation rates may be because we excluded patients (twelve in total) with limb threatening DFU, and those with suspected osteomyelitis as well as those with sign or symptoms of necrotizing fasciitis, SIRS or gangrene on video examination.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Other authors have also noticed an increased rates of major or minor amputations during the pandemic period attributed to predominantly ischemic ulcers or non infected DFU [ 23 25 ]. The amputation rates in our study was significantly less as compared to that observed by Caruso P, et al [ 21 ] and Schmidt et al [ 22 ] despite the inclusion of patients with active DFU (either ischemic or neuropathic) with or without DFI. Probable reasons for lesser amputation rates may be because we excluded patients (twelve in total) with limb threatening DFU, and those with suspected osteomyelitis as well as those with sign or symptoms of necrotizing fasciitis, SIRS or gangrene on video examination.…”
Section: Discussioncontrasting
confidence: 78%
“…A hospital based study of patients coming to emergency department with severe DFU during COVID-19 pandemic observed three-fold higher risk of limb amputation as compared to the similar period in year 2019 (60% vs 18%, p = 0.001) [ 21 ]. Another study observed a similar number (24.25%) of minor amputation following foot ulcers during COVID-19 pandemic compared to (20.5%, p>0.05) pre-pandemic period [ 22 ]. Other authors have also noticed an increased rates of major or minor amputations during the pandemic period attributed to predominantly ischemic ulcers or non infected DFU [ 23 25 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…3 Similar strategies have been adopted in the United States, Turkey and India. 4,9,10 A multidisciplinary team in Zhejiang, China, developed an internet-based programme to manage people with DFU which included regular instant messaging and remote consultations. 11 A report from Italy, from a region which experienced severe impacts from COVID-19, including strict lockdown and significant interruption to outpatient services, described a marked increase in gangrene and amputations amongst patients hospitalised for DFU, highlighting the risk to patients with DFU from interruptions to usual podiatry and IHRF care.…”
Section: Discussionmentioning
confidence: 99%
“…2 The pandemic has led to significant stress on hospital systems worldwide and delays to acute hospital care for people with diabetes and diabetes-related complications. 3,4 People with diabetes are at higher risk of COVID-19 and its complications. [3][4][5]…”
mentioning
confidence: 99%